2019
DOI: 10.1519/jsc.0000000000002121
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between a Jump-Landing Task and Functional Movement Screen Items : A Validation Study

Abstract: Sports injuries and athletic performance are complex areas, which are characterized by manifold interdependencies. The landing error scoring system (LESS) is a valid screening tool to examine bilateral jump-landing mechanics. Whereas, the Functional Movement Screen (FMS) items are thought to operationalize flexibility and motor behaviour during low intense bodyweight patterns. The aim of the study was to explore possible interdependency of the diagnostic information of these screening tools. 53 athletes (age 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…1 Changes in box height would likely affect LESS scores to a greater extent than changes in landing distance. Some authors have used a 40cm rather than a 30-cm box 28 and tested participants barefoot 29 during the LESS, but the clinical implications of these alterations compared with the original protocol are unknown. 1 Whereas the odds of being classified as at high injury risk were similar between the d 50% and d ss conditions at a group level (P ¼ .859) based on the established cutoff score of 5 errors, 1 only a subset of individuals (n ¼ 34, 49%) were categorized as at high risk under both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1 Changes in box height would likely affect LESS scores to a greater extent than changes in landing distance. Some authors have used a 40cm rather than a 30-cm box 28 and tested participants barefoot 29 during the LESS, but the clinical implications of these alterations compared with the original protocol are unknown. 1 Whereas the odds of being classified as at high injury risk were similar between the d 50% and d ss conditions at a group level (P ¼ .859) based on the established cutoff score of 5 errors, 1 only a subset of individuals (n ¼ 34, 49%) were categorized as at high risk under both conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Another important limitation is that populations included, testing protocols, and calculations of total LESS score varied across studies. Population characteristics—for example, age, sex, and activity level—can significantly influence LESS scores, 3,27,53 and therefore the results of this literature review are most relevant to uninjured military freshmen and sportspeople with a mean age between 14 and 28 years.…”
Section: Discussionmentioning
confidence: 99%
“…The Landing Error Scoring System (LESS; Appendix Table A1, available in the online version of this article) is a clinical assessment tool 40 often used in research to identify individuals at high risk of sustaining noncontact injuries and to quantify changes in neuromuscular and biomechanical performance subsequent to intervention across sports 14,15,18 and performance levels. 27,49 The LESS has also been used in participants with a history of injury 24,30 and after anterior cruciate ligament (ACL) reconstruction 2,20 to quantify residual functional impairments and outcomes from rehabilitation.…”
mentioning
confidence: 99%
“…The NOS adapted for cross-sectional studies was used for 33 (64%) studies. Out of a maximum of 10 stars, 2 studies scored two stars 35,39 , 4 studies four stars [40][41][42][43] , 7 studies five stars [44][45][46][47][48][49][50] , 10 studies six stars 1,18,32,37,38,[51][52][53][54][55] , 2 studies seven stars 56,57 , 7 studies eight stars 4,5,19,33,[58][59][60] , and 1 study nine stars 6 . The RoB 2 was used for 9 (17%) studies.…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…Only Smith et al 5 compared overall LESS scores between different age categories and reported significantly lower overall LESS scores in older college athletes compared to younger high school athletes. Seven studies 4,6,7,14,61,62,66 tested and reported overall LESS scores for 1,997 participants 15 years or younger; 17 studies 5,15,18,31,33,36,38,45,46,49,52,56,58,63,64,67,70 for 1,613 participants aged from 15 to 20 years inclusively; and 24 studies 8,17,19,[32][33][34][35]37,[39][40][41][42][43][44]47,48,51,55,57,59,60,65,67,68 for 4,566 participants older than 20 years. The weighted mean LESS scores...…”
Section: Agementioning
confidence: 99%